Adipose-Derived Stem Cells Pretreated With Phototherapy Promote HUVECs Migration and Angiogenesis by Mediating EYA1 Activation. - Dan ZHANG; Yi ZHANG; Jia WEN; Biling WU; Youwen CHEN; Yuejiao SONG; Chao LIANG (Physiological Research, 2025)
Promoting angiogenesis to enhance the success rate of parathyroid autotransplantation represents an effective strategy for improving patient outcomes following thyroid surgery. Eyes absent homolog 1 (EYA1) may be modulated by stromal vascular fraction (SVF) and adipose-derived stem cells (ADSCs) to facilitate angiogenesis. Phototherapy, which involves the use of artificial light source irradiation for disease prevention and treatment, has emerged as a promising approach. However, it remains unclear whether ADSCs pretreated with phototherapy can promote angiogenesis in the parathyroid gland through the regulation of EYA1. Primary human ADSCs (hADSCs) were isolated and identified. The impact of various wavelengths of light on the proliferation and secretion of angiogenic factors by hADSCs was assessed using a CCK-8 assay and an ELISA. Subsequently, the influence of light-pretreated hADSCs on HUVEC proliferation, migration, and angiogenesis was evaluated through CCK-8, Transwell, tube formation assays, and ELISA. Finally, qRT-PCR and Western blot analysis were employed to examine the effects of different wavelengths of light on the expression levels of differentiation-related transcription factors in hADSCs, including EYA1. To further elucidate the role of EYA1, an EYA1 interference plasmid (si-EYA1) and its negative control plasmid (si-NC) were transfected into hADSCs to determine whether silencing EYA1 would inhibit the promotion of HUVECs migration and angiogenesis by light-pretreated hADSCs. The results demonstrated that compared with green light (516 nm) and blue light (475 nm), red light (635 nm) irradiation significantly enhanced hADSCs proliferation and the secretion of angiogenic factors. Moreover, light-pretreated (red light) hADSCs markedly promoted HUVECs proliferation, migration, and angiogenesis. Additionally, red light irradiation significantly upregulated the mRNA and protein expression of EYA1, SIX1, TGF-ß1, and Wnt1 while downregulating the mRNA and protein expression of DACH1 in hADSCs. However, silencing EYA1 attenuated the promotive effect of light-pretreated hADSCs on HUVECs migration and angiogenesis. These findings suggest that phototherapy-pretreated hADSCs may enhance HUVECs migration and angiogenesis via the activation of EYA1 and increased secretion of angiogenic factors.